Use of space maintainers and recoverers in interceptative orthodontics: Review of current concepts (Research, Society and Development, 2020)
The primary dentition is essential for good performance in masticatory functions, swallowing, phonation and occlusion. There are several factors that can interfere with the balance of the development of primary and / or mixed dentition, among these factors the premature loss of primary ones stands out. The aim of this study was to conduct a literature review addressing the use of space maintainers and retrievers in dentistry. According to the literature, it was observed that space maintainers are orthodontic devices used in order to replace one or more primary teeth, preserving the space for the successor permanent tooth. They are classified as functional and non-functional and fixed and removable, being selected according to the patient's age and number of missing teeth. Recuperators are dynamic orthodontic devices, and their purpose is to recover spaces that were lost after extraction of primary teeth. It is essential that the dentist performs an early diagnosis of problems arising from space in deciduous or mixed dentitions, knowing the etiological factors involved in premature loss, as well as the orthodontic treatment options available.